PHASE IDENTEFATION OF INCONEL 738 LC SUPERALLOY BY ACTIVE BRAZING ALLOY OF (28 Ni 72 Ti) - Mohammed, Mudhafer (Gebze Teknik Üniversitesi, 2020)
In this study, Inconel 738LC superalloy brazed by (28Ni72Ti) which was used as an active filler alloy at temperature  at  985ºC  for  (15min) this process achieved  in a furnace  brazing  under high purity of a protective gas (99.999 Argon gas)  to ensure   that  joints  free from  oxidation   and  contamination.   The XRD and   microstructure  analysis  was  implemented   to  investigate  the  bonding  morphology  and   the bonding strength was estimated from shear  test. The results illustration that highest shear strength was 29 MPa and  the morphologically  the  strength of  bonding  was  inclined by  the creation  of  reaction  layers that  cross over in the center of   the  brazing area  due to the  interdiffusion effects of  several constituents from base  metal (738 superalloy ) and active brazed metal (28Ni72Ti).Use of word processing software It is important that the file be saved in the native format of the word processor used. The text should be in single-column format. Keep the layout of the text as simple as possible. Most formatting codes will be removed and replaced on processing the article. In particular, do not use the word processor's options to justify text or to hyphenate words. However, do use bold face, italics, subscripts, superscripts etc. When preparing tables, if you are using a table grid, use only one grid for each individual table and not a grid for each row. If no grid is used, use tabs, not spaces, to align columns. The electronic text should be prepared in a way very similar to that of conventional manuscripts Note that source files of figures, tables and text graphics will be required whether or not you embed your figures in the text. See also the section on Electronic artwork. To avoid unnecessary errors you are strongly advised to use the 'spell-check' and 'grammar-check' functions of your word processor. Article structure General guidelines for online submission: Elsevier can accept text files in most standard word-processing formats but Microsoft Word is preferred. All online submissions must be accompanied by a covering letter detailing what you are submitting. Please indicate the author to whom correspondence should be addressed (in the case of multiple authors) and include a contact address, telephone/fax numbers for the corresponding author and e-mail addresses for all authors. Length of papers Published articles are normally less than 10 printed pages; this approximately equals a typewritten paper of 20 double-spaced pages plus a typical number of figures (8 or so). Use double spacing and minimum 1-inch (3 cm) margins, and 12 pt font size standard fonts. Pagination Please ensure that your manuscript is paginated, as this will help both editors and reviewers to process it promptly. Subdivision - numbered sections Divide your article into clearly defined and numbered sections. Subsections should be numbered 1.1 (then 1.1.1, 1.1.2, ...), 1.2, etc. (the abstract is not included in section numbering). Use this numbering also for internal cross-referencing: do not just refer to 'the text'. Any subsection may be given a brief heading. Each heading should appear on its own separate line. As a general guideline, the preferred order for sections is: abstract, introduction, experimental, results, discussion, conclusion, acknowledgements, references, appendices. Introduction Provide a critical assessment of the literature relevant to the problem at hand, delineating unresolved issues. State clear objectives to explain how this study will take the field forward. Experimental Provide sufficient detail to allow the work to be reproduced. Methods already published should be indicated by a reference: only relevant modifications should be described.Error bars: Error bars are required on all experimental and calculated data points with an explanation in the text as to how the errors were determined. SI Units SI units should be used throughout. Theory/calculation A Theory section should extend, not repeat, the background to the article already dealt with in the Introduction and lay the foundation for further work. In contrast, a Calculation section represents a practical development from a theoretical basis. Results Results should be clear and concise. Discussion Should develop cogent explanation for the results and explore their significance. In the case of computational studies, results should be compared with information available from published experimental work, if possible. Conclusions The main conclusions of the study may be presented in a short Conclusions section, which should stand alone. Appendices If there is more than one appendix, they should be identified as A, B, etc. Formulae and equations in appendices should be given separate numbering: Eq. (A.1), Eq. (A.2), etc.; in a subsequent appendix, Eq. (B.1) and so on. Similarly for tables and figures: Table A.1; Fig. A.1, etc. Essential title page information • Title. Concise and informative. Titles are often used in information-retrieval systems. Avoid abbreviations, acronyms and formulae where possible. • Author names and affiliations. Where the family name may be ambiguous (e.g., a double name), please indicate this clearly. Present the authors' affiliation addresses (where the actual work was done) below the names. Indicate all affiliations with a lower-case superscript letter immediately after the author's name and in front of the appropriate address. Provide the full postal address of each affiliation, including the country name and, if available, the e-mail address of each author. Author names may not be added after a paper has been accepted. • Corresponding author. Clearly indicate who will handle correspondence at all stages of refereeing and publication, also post-publication. Ensure that phone numbers (with country and area code) are provided in addition to the e-mail address and the complete postal address. Contact details must be kept up to date by the corresponding author. • Present/permanent address. If an author has moved since the work described in the article was done, or was visiting at the time, a 'Present address' (or 'Permanent address') may be indicated as a footnote to that author's name. The address at which the author actually did the work must be retained as the main, affiliation address. Superscript Arabic numerals are used for such footnotes. •It is not necessary to submit the title page as a separate document. However, if this option is chosen, please also include title page information at the beginning of the text document. Abstract An abstract is required for all papers. The abstract should indicate the content of the paper, and should describe the main conclusions. An effective abstract is brief and normally less than 250 words. Abstracts should not exceed 300 words. References should be avoided, but if essential, they must be cited in full, without reference to the reference list. Graphical abstract Graphical abstracts are not accepted for this journal. Keywords Immediately following the Abstract, provide a maximum of 5 keywords which appropriately represent the contents of the paper. Abbreviations Define abbreviations and acronyms when they first appear in the article. Ensure consistency of abbreviations throughout the article. Acknowledgements Collate acknowledgements in a separate section at the end of the article before the references and do not, therefore, include them on the title page, as a footnote to the title or otherwise. List here those individuals who provided help during the research (e.g., providing language help, writing assistance or proof reading the article, etc.). Math formulae Please submit math equations as editable text and not as images. Present simple formulae in line with normal text where possible and use the solidus (/) instead of a horizontal line for small fractional terms, e.g., X/Y. In principle, variables are to be presented in italics. Powers of e are often more conveniently denoted by exp. Number consecutively any equations that have to be displayed separately from the text (if referred to explicitly in the text). Artwork Electronic artwork General points • Make sure you use uniform lettering and sizing of your original artwork. • Embed the used fonts if the application provides that option. • Aim to use the following fonts in your illustrations: Arial, Courier, Times New Roman, Symbol, or use fonts that look similar. • Number the illustrations according to their sequence in the text. • Use a logical naming convention for your artwork files. • Figures and captions to illustrations should be submitted on the same page. • Size the illustrations close to the desired dimensions of the published version. • Submit each illustration as a separate file. .You are urged to visit this site; some excerpts from the detailed information are given here.Formats If your electronic artwork is created in a Microsoft Office application (Word, PowerPoint, Excel) then please supply 'as is' in the native document format. Regardless of the application used other than Microsoft Office, when your electronic artwork is finalized, please 'Save as' or convert the images to one of the following formats (note the resolution requirements for line drawings, halftones, and line/halftone combinations given below): EPS (or PDF): Vector drawings, embed all used fonts. TIFF (or JPEG): Color or grayscale photographs (halftones), keep to a minimum of 300 dpi. TIFF (or JPEG): Bitmapped (pure black and white pixels) line drawings, keep to a minimum of 1000 dpi. TIFF (or JPEG): Combinations bitmapped line/half-tone (color or grayscale), keep to a minimum of 500 dpi.Please do not: • Supply files that are optimized for screen use (e.g., GIF, BMP, PICT, WPG); these typically have a low number of pixels and limited set of colors; • Supply files that are too low in resolution; • Submit graphics that are disproportionately large for the content. Color artwork Please make sure that artwork files are in an acceptable format (TIFF (or JPEG), EPS (or PDF), or MS Office files) and with the correct resolution. If, together with your accepted article, you submit usable color figures then Elsevier will ensure, at no additional charge, that these figures will appear in color online (e.g., ScienceDirect and other sites) regardless of whether or not these illustrations are reproduced in color in the printed version. For color reproduction in print, you will receive information regarding the costs from Elsevier after receipt of your accepted article. Please indicate your preference for color: in print or online only. Figure captions Ensure that each illustration has a caption. Figures and captions should be submitted on the same page. A caption should comprise a brief title (not on the figure itself) and a description of the illustration. Keep text in the illustrations themselves to a minimum but explain all symbols and abbreviations used. Tables Please submit tables as editable text and not as images. Tables can be placed either next to the relevant text in the article, or on separate page(s) at the end. Number tables consecutively in accordance with their appearance in the text and place any table notes below the table body. Be sparing in the use of tables and ensure that the data presented in them do not duplicate results described elsewhere in the article. Please avoid using vertical rules. References All references to other papers, books, etc., must be given at the end of the paper. They should be numbered in sequence starting at the beginning of the paper. The numbers (in brackets) should appear in the text at the appropriate places. Citation in text Please ensure that every reference cited in the text is also present in the reference list (and vice versa). Any references cited in the abstract must be given in full. Unpublished results and personal communications are not recommended in the reference list, but may be mentioned in the text. If these references are included in the reference list they should follow the standard reference style of the journal and should include a substitution of the publication date with either 'Unpublished results' or 'Personal communication'. Citation of a reference as 'in press' implies that the item has been accepted for publication. Web references As a minimum, the full URL should be given and the date when the reference was last accessed. Any further information, if known (DOI, author names, dates, reference to a source publication, etc.), should also be given. Web references can be listed separately (e.g., after the reference list) under a different heading if desired, or can be included in the reference list. Data references This journal encourages you to cite underlying or relevant datasets in your manuscript by citing them in your text and including a data reference in your Reference List. Data references should include the following elements: author name(s), dataset title, data repository, version (where available), year, and global persistent identifier. Add [dataset] immediately before the reference so we can properly identify it as a data reference. The [dataset] identifier will not appear in your published article. Reference style Text: Indicate references by number(s) in square brackets in line with the text. The actual authors can be referred to, but the reference number(s) must always be given. Example: '..... as demonstrated [3,6]. Barnaby and Jones [8] obtained a different result ....' List: Number the references (numbers in square brackets) in the list in the order in which they appear in the text. Please include all author names. Please include article titles of all cited articles as in the following examples. Examples: Reference to a journal publication: [1] J. van der Geer, J.A.J. Hanraads, R.A. Lupton, The art of writing a scientific article, J. Sci. Commun. 163 (2010) 51–59. Reference to a book: [2] W. Strunk Jr., E.B. White, The Elements of Style, fourth ed., Longman, New York, 2000. Reference to a chapter in an edited book: [3] G.R. Mettam, L.B. Adams, How to prepare an electronic version of your article, in: B.S. Jones, R.Z. Smith (Eds.), Introduction to the Electronic Age, E-Publishing Inc., New York, 2009, pp. 281–304. [dataset] [4] M. Oguro, S. Imahiro, S. Saito, T. Nakashizuka, Mortality data for Japanese oak wilt disease and surrounding forest compositions, Mendeley Data, v1, 2015. http://dx.doi.org/10.17632/xwj98nb39r.1.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri